A Mini Review on the Current Status of Leishmaniasis and the Need to Prioritize Research on Establishing Reservoir Hosts in Sri Lanka - Kannathasan, S.; Murugananthan, A.; Shivaganesh, S. (University of Jaffna, 2024)
Since the first report of leishmaniasis from Sri Lanka in 1992, the number of notified cutaneous leishmaniais (CL) cases increases considerably from all 25 districts of the country. It was established that the parasite responsible for CL is Leishmania donovani zymodem MON-37; the species which causes the fatal Visceral Leishmaniasis (VL) around the world and the vector for this species is Phlematous argentipes (Diptera: Psychodidae: Phlebotominae). In addition, reports suggest the emergence of fatal VL in the country. The impact of the disease burden hampers human resources and leads to economic loss in the country. After declaring leishmaniasis as a notifiable disease in 2008, the health authorities started to implement preventive strategies to control the disease in the Island. However, achieving the goal posts challenges in terms of diagnosis, treatment, vector control and preventing vector human contact. With this background, this mini review focuses on the importance of establishing the reservoir hosts in different localities in Sri Lanka. Hence, this knowledge can be utilized as one of the major components in the existing control strategy for controlling the disease in the country.
Keywords: Leishmaniasis; Cutaneous Leishmaniasis; Reservoir Hosts